Fostering transformational leadership among young adults: a basic psychological needs approach. Issue 3 (2nd July 2016) - Perreault, Dominique; Cohen, Lori R.; Blanchard, Céline M.
Abstract: Scholars have noted the constructive effects of transformational leadership on groups and organisations. Key predictors of transformational leadership include aspects of personality, self-concept, as well as social context. The purpose of this research was to support and extend past work by exploring the links between a supportive social context, leadership traits, self-efficacy and transformational leadership on a sample of university students (Study 1, n = 397) and testing the replicability of the findings (Study 2, n = 392) while controlling for intelligence. Results from both studies supported the hypothesis that the experience of basic psychological need satisfaction plays a moderating role in the relation between a leader's personality, self-efficacy and transformational leadership. Discussion emphasises keys findings and highlights implications for theory, research and practice.